PREDIKSI KETENAGAKERJAAN DAN SEKTOR PERTANIAN DI INDONESIA TAHUN 2009 SERTA ANTISIPASI TERHADAP ANCAMAN KRISIS GLOBAL - Sonny Harry B. Harmadi; Prijono Tjiptoherijanto (Jurnal Kependudukan Indonesia, 2009)
The threat of a global crisis that began to be felt now estimated to have a ~ignificant impact on employment issues, but not so with the agricultUral sector in Indonesia. The decline in aggregate demand leads to slowing growth in real sector and must have a direct effect on employment. Predicted unemployment would rise and certainly has implications for the stability of national economy. Therefore it needs a variety of anticipation, including with fiscal stimulus to reduce the perceived impact of the Indonesian economy. It is the general case that the declfue in activity in the formal sector because of the crisis caused many workers to switch to the informal sector, particularly agriculture. Proven agricultural sector during the economic crisis and still be positive growth and not much affected by the crisis. However agriculture remains a vital sector, given the role of national food security .. Slowing the formal sector activity causes land conversion from agricultural land to non-agriculture will be reduced. In addition, the output of the agricultural sector will increase and of course the national food security is expected to still be maintained.Keywords: labor, agriculture, unemployment, food security, global crisis, fiscal stimulus.